Building bridges to female - and youth-inclusive employment: the influence of cash transfers for ex-combatants - Blanca Zuluaga; Paola Palacios (Development Studies Research)
The ability of ex-combatants to engage in sustainable income-generating activities is a central pillar of successful demobilization, disarmament, and reintegration processes, even though full reintegration also requires progress in social, political, and psychological dimensions. However, there is limited quantitative evidence on which strategies effectively support economic reintegration. In 2011, Colombia introduced a one-time cash transfer aimed at helping ex-combatants access employment or start a business. Using administrative and survey data on labor market outcomes and socio-economic characteristics, we evaluate the impact of this policy using the Propensity Score Matching method. We find that the cash transfer significantly increases the probability of employment. The effect is particularly strong among young and female ex-combatants, highlighting the need for targeted support for these groups. Our findings underscore the positive role that financial assistance can play in reintegration efforts and offer useful insights for the design of future DDR programs.